Le nouveau testament Based on a Play by Sacha Guitry - Guitry, Sacha; Bachelet, Jean; Delubac, Jacqueline; Daussmond, Betty (Sacha Guitry: L'âge d'or (1936-1938), 2012)
This is Guitry in urban mode which means sophisticated well-dressed people sitting in salons dishing dirt and playing sexual games. The only thing that comes anywhere near Guitry in this mode is Noel Coward and even that is slightly misleading; they were both primarily playwrights, yes, and they tended to write with a swizzle stick rather than a pen, yes again, but really they were chalk and cheese. This is prime Guitry, nuff said. [edinburghfilmguild.org.uk]